On the puzzling arrangement of the asymmetric MalT-binding sites in the MalT-dependent promoters. - Danot, O (1993)
The MalT-dependent promoters of the enterobacteria belong to a small family of positively regulated prokaryotic promoters in which the activator protein recognizes short asymmetric nucleotide sequences present in several locations and orientations. We demonstrate that active MalT-dependent semisynthetic promoters can be constructed by using a synthetic decanucleotide as the MalT site and random nucleotide sequences as connecting sequences, provided that the location and orientation of the sites are the same as in natural MalT-dependent promoters. Strikingly, the induced level of promoter activity and the induction factor of each semisynthetic promoter are identical to those of its natural counterpart, in spite of considerable differences in their nucleotide sequences. The study of these semisynthetic promoters confirms the importance of the structural motif formed by two MalT sites in a direct repeat. This motif is involved in promoter activation either alone or in conjunction with a third MalT site, proximal with respect to the transcription start site. In this latter configuration, the promoters are active irrespective of the orientation of the repeat, and they retain at least some activity when the distance between the repeat and the proximal site is increased, provided that the alignment along the axis of the helix is conserved.